LEETECH facility as a flexible source of low energy electrons - D. Attie; S. Barsuk; O. Bezshyyko; L. Burmistrov; A. Chaus; P. Colas; O. Fedorchuk; L. Golinka-Bezshyyko; I. Kadenko; V. Krylov; V. Kubytskyi; R. Lopez; et al. (Ядерна фізика та енергетика)
A new versatile facility LEETECH for detector R&D, tests and calibration is designed and constructed. It uses electrons produced by the photoinjector PHIL at LAL, Orsay and provides a powerful tool for wide range R&D studies of different detector concepts delivering “mono-chromatic” samples of low energy electrons with adjustable energy and intensity. Among other innovative instrumentation techniques, LEETECH will be used for testing various gaseous tracking detectors and studying new Micromegas/InGrid concept which has very promising characteristics of spatial resolution and can be a good candidate for particle tracking and identification. In this paper the importance and expected characteristics of such facility based on detailed simulation studies are addressed.